The Impact of Emotional Intelligence on the Psychological Well-Being of Young Graduates in Portugal - Manuela Larguinho; Sandrina Leal; Rita Lopes (Psychology International, 2025)
Background: The present research seeks to understand the impact of emotional intelligence on the psychological well-being of young graduates Well-being is closely linked to happiness and life satisfaction and occurs when individuals possess adequate psychological, social, and physical resources to manage life’s challenges. Emotional Intelligence, defined as the ability to recognize, understand, and regulate emotions, has been identified as a key factor influencing psychological well-being. Research highlights that individuals with higher emotional intelligence tend to experience greater life satisfaction, lower stress levels, and improved mental health. However, the specific impact of emotional intelligence on the psychological well-being of young graduates remains underexplored, particularly in the Portuguese context, making this study highly relevant. Methods:To investigate this impact, a questionnaire was administered to a sample of 209 young graduates in Portugal, which included emotional intelligence and psychological well-being items and a multiple regression model was used. Results: the results obtained indicate that emotional intelligence has a statistically significant influence on psychological well-being, where young people with higher levels of emotional intelligence showed higher levels of psychological well-being. Regarding age and sex, our data did not show a statistically significant relationship with emotional intelligence or psychological well-being. Conclusions: In summary, this study confirmed that young people with greater ability to manage their own emotions are more likely to experience higher psychological well-being.